Disaster Emergency Response Management to Anticipate the Spread of Covid-19 at the Islamic Boarding School - Ifendi, Mahfud (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Islamic boarding schools, known as Islamic educational institutions, that are characterized by their Indonesian identity, must continue to exist, and survive all forms of change and challenges of the times. Covid-19, which has come to destroy all aspects of life, has created and forced Islamic boarding schools to survive in carrying out their education. Through a qualitative approach, this research was carried out. The data collection was taken by interview, observation, and documentation. Data analysis used data condensation, data display, and drawing and verifying conclusions. The results of the research in this article are that what Daarul Ikhlas Sangatta Selatan Islamic boarding school does to anticipate the spread of covid-19 is implemented in planning, organizing, implementing, and supervising. To overcome the spread of covid-19 in Islamic boarding schools, what is being done is to implement health protocols in a disciplined and strict manner according to what is recommended by the central government or by the Indonesian Rabithah Ma'hadiyah Nahdlatul Ulama (RMI NU) in every activity in the Islamic boarding school environment.